Operational Planning of 'Remedies' Postpartum Care Center: Ensuring of Service Providing to Consumers - Martianto, Yudha Hartlanda; Indradewa, Rhian; Kustiawan, Unggul; Pamungkas, Rian Adi (Politeknik Siber Cerdika Internasional, 2025)
Remedies Postpartum Care Center aims to provide holistic healthcare services for postpartum mothers, especially during the critical period of 0-14 days after delivery. During this period, mothers usually experience various physical, mental, and emotional challenges that require special attention. Remedies offers comprehensive services, including psychological consultation, nutritional care, lactation support, and recovery facilities with modern technology. With a structured operational planning strategy, Remedies strives to be a high-quality postpartum healthcare provider and provide a memorable experience for consumers when receiving services at Remedies. To ensure the effectiveness of care, the operational planning implemented includes human resource management, facility optimization, and the use of digital-based technology to improve service quality. In terms of marketing, Remedies utilizes digital strategies to raise public awareness of the importance of postpartum care, while expanding the reach of services to more mothers who need intensive support. Research on the effectiveness of postpartum care shows that holistic services such as those offered by Remedies can significantly improve the physical and mental recovery of mothers. With a data-driven approach and digital marketing strategy, Remedies plans to increase market share and become a leader in the industry. Thus, mature operational planning will contribute to creating more optimal and sustainable health services for postpartum mothers.